2005
DOI: 10.1200/jco.2004.00.9787
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Prevention of Catheter-Related Bloodstream Infection by Continuous Infusion of Low-Dose Unfractionated Heparin in Patients With Hematologic and Oncologic Disease

Abstract: The use of continuous infusion of low-dose unfractionated heparin (100 U/kg per day) can be a practical and economical approach to the prevention of catheter-related bloodstream infection in patients with hemato-oncological disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…In addition, one randomized trial [20] found that intravenous doses of unfractionated heparin in patients with hematologic and oncologic disease, with a nontunneled catheter, did prevent CR-BSIs, suggesting that the antifibrin effect rather than any other specific property of warfarin is what helps prevent infection. From the pathogenic viewpoint, increasing importance is in fact being attached to the biofilm's role in favoring and maintaining bacterial colonization [21] and fibrin appears to be vital in the formation of this matrix [22].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, one randomized trial [20] found that intravenous doses of unfractionated heparin in patients with hematologic and oncologic disease, with a nontunneled catheter, did prevent CR-BSIs, suggesting that the antifibrin effect rather than any other specific property of warfarin is what helps prevent infection. From the pathogenic viewpoint, increasing importance is in fact being attached to the biofilm's role in favoring and maintaining bacterial colonization [21] and fibrin appears to be vital in the formation of this matrix [22].…”
Section: Discussionmentioning
confidence: 96%
“…34 Catheter-related infections may be caused by fibrin deposition associated with these catheters and interventions to decrease fibrin deposition could reduce infections. In a recent study in 208 patients 33 the use of low-dose unfractionated heparin resulted in significant less catheter-related infections (6.8 vs 16.6%). Another alternative is a peripherally inserted catheter or a totally implanted venous access port (VAP).…”
Section: Discussionmentioning
confidence: 99%
“…Aseptic techniques for handling the catheters, 27 skin disinfection, 28 impregnating catheters with antibiotics or the use of anticoagulation [29][30][31][32][33] have been proven of value. A study of 356 non-tunneled catheters in cancer patients showed that impregnation of central venous catheters with minocycline and rifampicin was efficacious (3 vs 14 infections in impregnated vs nonimpregnated catheters) and safe in reducing catheter-related infections.…”
Section: Discussionmentioning
confidence: 99%
“…16 The clot prevention strategies are effective reducing the rate of CRB. 17 A first study has evaluated LMWH for hemodialysis catheter lock (tinazaparin) and suggests that could be a potential alternative 18 but more studies are needed to better define the role of LMWH for hemodialysis catheter lock. Citrato is also used as anticoagulant with extra antimicrobial or biofilm removing properties, in contrast to heparin which even tend to antagonize the bactericidal properties of certain antibiotics and promotes biofilm formation.…”
Section: Catheter Related Bacteraemia (Crb)mentioning
confidence: 99%